(3JGQjN GdSdWGf Sdje GdYKeGfj eY GdSdWGf bGfUhI GdZhQjs - (3CMeO Hf Ydj Hf CMeO Hf RfHd GdQeGd , J HYO (B980 (3g` s ((3Ydj GdeGdcj s)
(3ChdgG (B:s
(3hHYO abO SFd GdabjQ Edi QMeI Gddg JYGdi GdTjN eMeO GdRfHdi GdQeGd Cf jDda SjQI Gdedc GdCTQa GdSdWGf GdZhQi eY GdSdWGf Sdje NGf heG hbY dgeG ef GdMQhH s
(3BNQgG (B:s
(3hdeG eGJ QMeg Gddg JYGdi Jhdi eMeO HGTG, Ke Jhdi Ydi HGTG heGJ HeUQ , hOaf HLGfH GdbGVi HcGQ, hgde LQG Edi jhefG gPG s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B180s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B298 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B409 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B468 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs